Implementasi Kebijakan Pondok Pesantren Ramah Anak: Tantangan dan Peluang di Era Modern - Mahmudi, Moh; Abdulah, Fernanda Setya Putra; Hayat (Jejaring Administrasi Publik, 2024)
Islamic boarding schools as religious-based educational institutions have a very strategic role in forming children's character and spiritual values. This research aims to explore the implementation of policies regarding Child-Friendly Islamic Boarding Schools, as well as the challenges and opportunities faced in the modern context. This research method uses literature study by collecting several journals related to the title and focus of the research raised. By analyzing various academic sources and related policies, this research identified that the challenges faced include: lack of understanding of child protection, understanding of gender, and limited access to information in remote areas. On the other hand, there are opportunities that arise from increasing public attention to children's rights, support for government policies, and technological innovation that can support the sustainability of education. The study results show that collaboration between educational institutions, government and society is very important to optimize the implementation of this policy. In this way, it is hoped that Islamic Boarding Schools can be transformed into places that are child-friendly, comfortable and successful in supporting their growth. Keywords: Boarding School, Policy, Child Friendly